The Instructional Planning and Effective Lesson Delivery: Teachers’ Experiences and Pedagogical Perspectives in Public Secondary Schools of the City of Ilagan, Philippines: None - LACISTE, JOEMAR; Paragas, Benjamin (Studies in Technology and Education, 2026)
Effective instructional planning and lesson delivery are essential elements of quality teaching and meaningful learning experiences in secondary education. This qualitative study explored the experiences and pedagogical perspectives of teachers regarding instructional planning and effective lesson delivery in public secondary schools in the City of Ilagan, Philippines. Specifically, the study examined the instructional strategies employed by teachers, the challenges encountered in lesson implementation, and the pedagogical practices perceived as effective in facilitating learner engagement and academic participation. The study utilized a qualitative phenomenological research design involving twelve public secondary school teachers selected through purposive sampling. Data were gathered through semi-structured interviews, classroom observations, and document analysis of lesson plans and instructional materials. Thematic analysis following Braun and Clarke’s framework was employed in analyzing the gathered data. Findings revealed that teachers emphasized learner-centered instructional planning, contextualized and differentiated teaching approaches, collaborative and experiential learning strategies, reflective instructional adjustment, and classroom interaction as essential dimensions of effective lesson delivery. However, teachers also experienced challenges related to time constraints, large class sizes, limited instructional resources, and diverse learner needs. Despite these constraints, teachers demonstrated adaptability, creativity, and commitment in delivering meaningful learning experiences. The study highlights the importance of strengthening instructional support systems, professional development programs, and resource accessibility to enhance pedagogical effectiveness in Philippine public secondary schools.